The treatment of the indebted person in courts after Civil and Commercial Code (2015–2020) (Nueva Epoca, 2020)
The indebted person is a human person who cannot exercise his right to free himself from one or more debts, which not only weigh on his assets but also on other aspects of his personhood. In this work we will analyze some judicial decisions issued after Civil and Commercial Code (2015–2020) that have applied different tools to protect indebted people.
Keywords: Private Law; Obligations Law; Civil and Commercial Code; Debt; Judicial Decisions; Indebted Person